2013
DOI: 10.1371/journal.pone.0075333
|View full text |Cite
|
Sign up to set email alerts
|

Brain Docosahexaenoic Acid [DHA] Incorporation and Blood Flow Are Increased in Chronic Alcoholics: A Positron Emission Tomography Study Corrected for Cerebral Atrophy

Abstract: ObjectiveChronic alcohol dependence has been associated with disturbed behavior, cerebral atrophy and a low plasma concentration of docosahexaenoic acid (DHA, 22∶6n-3), particularly if liver disease is present. In animal models, excessive alcohol consumption is reported to reduce brain DHA concentration, suggesting disturbed brain DHA metabolism. We hypothesized that brain DHA metabolism also is abnormal in chronic alcoholics.MethodsWe compared 15 non-smoking chronic alcoholics, studied within 7 days of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…It is possible that with prolonged α-LNA administration below 4.6%, k * may change in other lipid pools, or at dietary thresholds above 0.2% α-LNA. Also, dietary α-LNA thresholds and brain DHA requirements are likely to change during development, aging, liver malfunction, or the presence of neuropathological conditions, consistent with one study which reported increased k * for DHA in chronic alcoholics [53]. …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is possible that with prolonged α-LNA administration below 4.6%, k * may change in other lipid pools, or at dietary thresholds above 0.2% α-LNA. Also, dietary α-LNA thresholds and brain DHA requirements are likely to change during development, aging, liver malfunction, or the presence of neuropathological conditions, consistent with one study which reported increased k * for DHA in chronic alcoholics [53]. …”
Section: Discussionsupporting
confidence: 77%
“…We are aware of a few case studies of clinical n-3 PUFA deficiency in which patients receiving 0.02 to 0.09 % energy α-LNA (0.02% energy equals 0.66% of total fatty acids) through parenteral nutrition, developed neurological symptoms or dermatitis after a few months of being on the diet [4649]. Estimated α-LNA intakes in North America range between 0.64 to 0.73% of total energy [50, 51], which is within the 0.6–1.2 energy % range recommended by the Institute of Medicine [52], and likely meets the 2.1–3.8 mg daily rate of brain DHA consumption in humans established with positron emitting tomography (PET) [53, 54]. Worldwide intakes of α-LNA, however, vary by region and range between 0.1 to 1.4% energy (200–3000 mg/day) [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the development of fatty acid radiotracers for use in positron emission tomography (PET) has made possible the in vivo study of PUFA uptake into human brain. [1- 11 C]AA has been used to characterize unesterified AA incorporation into brain in healthy adults (Thambisetty et al, 2012), in aging (Esposito et al, 2007b; Giovacchini et al, 2002; Giovacchini et al, 2004; Rapoport et al, 2011; Umhau et al, 2009), and in patients with Alzheimer’s disease (Esposito et al, 2008); and during functional or pharmacological dopaminergic D2 receptor activation (Esposito et al, 2007a; Thambisetty et al, 2012), while [1- 11 C]DHA has been used to study baseline brain DHA consumption and chronic alcoholism (Umhau et al, 2013). Another new radiotracer, [ 18 F]-fluoroarachidonic acid (Pichika et al, 2012), is now under development.…”
Section: Brain Pufasmentioning
confidence: 99%
“…11C-palmitate PET has been used to study cardiac metabolism since the 80s [28], recent years have witnessed a great increase in metabolic PET studies as well as an increasing variety of tracers. For example, PET has recently been used to study brain fatty acid metabolism, using labeled heptadecanoate (18F-FTHA) [29] and docosahexanoic acid (11C-DHA) [30], providing interesting discoveries such as increased brain fatty acid uptake in humans with metabolic syndrome [29] and in chronic alcoholics [30]. The development of ketone PET tracers [31,32] likewise makes PET an increasingly relevant tool for addressing human ketone metabolism (see Fig.…”
Section: Role Of Pet In Human Metabolic Researchmentioning
confidence: 99%